2003
DOI: 10.1002/adma.200305034
|View full text |Cite
|
Sign up to set email alerts
|

Color Tunable Organic Light‐Emitting Diodes Using Pentafluorophenyl‐Substituted Iridium Complexes

Abstract: ordered and aligned lamellar phase structure of the synthesized monolithic silica. The SAXS pattern demonstrates that the order lamellar nanostructure of the prepared super-microporous silica does not collapse after removal of the template. Further work will be undertaken to employ the high robustness of the RTIL liquid-crystals for the generation of other mesoporous materials. ExperimentalPreparation of 1: The synthetic procedure of 1 followed a route reported in the literature [10]. 1-Chlorohexadecane (0.25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
132
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(136 citation statements)
references
References 19 publications
(36 reference statements)
4
132
0
Order By: Relevance
“…Tsuzuki et al reported other examples involving perfluorophenyl-substituted phenylpyridines. [14] Lin, Tao, and co-workers produced new benzoimidazoles and their bis-cyclometalated iridium(III) complexes in good yields following the described Nonoyama method. [157] These iridium complexes revealed strong phosphorescence at ambient conditions.…”
Section: Neutral Iridium(iii) Complexesmentioning
confidence: 98%
See 2 more Smart Citations
“…Tsuzuki et al reported other examples involving perfluorophenyl-substituted phenylpyridines. [14] Lin, Tao, and co-workers produced new benzoimidazoles and their bis-cyclometalated iridium(III) complexes in good yields following the described Nonoyama method. [157] These iridium complexes revealed strong phosphorescence at ambient conditions.…”
Section: Neutral Iridium(iii) Complexesmentioning
confidence: 98%
“…Here we will discuss the synthetic routes employed for the preparation of iridium(III) complexes utilized in phosphorescent LEDs. Currently, neutral cyclometalated complexes with modified and unmodified phenylpyridines [22,49] or acetylacetonate derivatives are very promising candidates for phosphorescent LEDs, [14] while mixed-ligand cyclometalated systems with diimines [146] resulting in charged species find applications in LECs. Regarding the synthesis of 2,2¢-bipyridine-containing ruthenium(II) complexes, the reader is referred to recent review articles.…”
Section: Different Synthetic Strategies Leading To Neutral and Chargementioning
confidence: 99%
See 1 more Smart Citation
“…[6,7,31] However, much milder reaction conditions have proved to work out as well, reducing the formation of side products, simplifying the purification procedure, and providing the opportunity to include more sensitive functionalities. Tsuzuki et al successfully synthesized a number of bis-cyclometallated iridium(III) acetoacetonate complexes by reacting the respective precursor and acetoacetone in a mixture with ethanol and Na 2 CO 3 at 50 8C for 2-6 h. [32] By replacing 2-ethoxyethanol with a non-alcoholic solvent in the coordination reactions of 2,7-dibromo-fluorene-functionalized acetoactone derivatives, Evans et al were able to avoid undesired hydrodebromination side reactions. Performing the reactions in acetonitrile at 80 8C in the presence of Na 2 CO 3 , the desired functionalized bis-cyclometallated acetoacetonate complexes were obtained in 74-81% yield after purification.…”
Section: Neutral Iridium(iii) Complexesmentioning
confidence: 99%
“…In phosphorescent devices, theoretically 100% internal quantum efficiency (IQE) is achieved by harvesting both singlet and triplet excitons generated by electrical injection which is four www.intechopen.com times that of fluorescent organic light-emitting devices (OLEDs) (Gong et al, 2002;Tsuzuki et al, 2003;Adachi et al, 2000). Förster and/or Dexter energy transfer processes (Tanaka and Tokito, 2008) between host and guest molecules play an important role in confining the triplet energy excitons in the phosphorescent guest.…”
Section: Ideal Host and Guest System 61 Introductionmentioning
confidence: 99%